The effects of lifestyle changes, sibutramine and orlistat in obese adults - Özgen, Metin; Özkan, Yusuf; Koca, Süleyman Serdar; Işik, Ahmet (My University, 2010)
Objective: Obesity is a low-grade chronic inflammatory process and the main risk factor for accelerated atherosclerosis and cardiovascular events. There is growing interest in cardiovascular disease associated with obesity and metabolic syndrome, accordingly, pharmacotherapy to overcome the increasing incidence of obesity. We aimed to compare the metabolic effects of lifestyle changes, sibutramine and orlistat in obese adults after the 6-months of therapy in this study. Material and Methods: Forty-eight obese adults were randomized into three groups (n= 16 for each). Lifestyle changes (low caloric diet, behavioral changes, and exercise) were recommended for all of the groups. Additionally, group II and III took sibutramine (15 mg/day) and orlistat (3x120 mg/day), respectively. Pre- and post-treatment anthropometric measurements were performed; Creactive protein (CRP), insulin resistance (HOMA-IR), and albuminuria levels were determined in the all of cases. Results: After the 6-month treatment, the mean weight loss was 5.3% in group I with lifestyle changes alone, 10.2% in group II (sibutramine group), and 8.4% in group III (orlistat group). In groups I, II, and III, body mass indexes (p< 0.05, p< 0.001, p< 0.001, respectively), waist circumferences (p< 0.05, p< 0.001, p< 0.001, respectively), and log-CRP (p< 0.05, p< 0.01, p< 0.01, respectively) decreased at the end of study. Furthermore, the HOMA-IR indexes decreased in the pharmacotherapy groups (p< 0.05 for both). Moreover, the reduction in log-albuminuria was significant (p< 0.01) in the sibutramine group, which had achieved the most weight loss. Conclusion: In obese adults, the use of pharmacotherapy in addition to lifestyle changes may effectively reduce cardiovascular risk factors such as inflammation and insulin resistance. Copyright © 2010 by Türkiye Klinikleri.
Keywords: Albuminuria; Insulin resistance; Life style; Obesity; Orlistat; Sibutramine